Sustainable Development and Human Capital - B. E. Israilov; M. A. Tursunmuratov (International Journal on Integrated Education, 2023)
This article analyzes the content of the concept of "human capital" and various views on it, and reveals its components and features. Also, comments were made on priority tasks aimed at the development of human capital in our country.